PERSEPSI PESERTA SUSCATIN TERHADAP BIMBINGAN PERKAWINAN DI KUA SINJAI UTARA KABUPATEN SINJAI - Burhanuddin Burhanuddin; Suriyati Suriyati; mustamir murtamir; ardianti ardianti (Universitas Islam Ahmad Dahlan, 2022)
This article aims to find out how the suscatin participants' perceptions of marriage guidance activities at the North Sinjai KUA office. Thisrresearch is a filedrresearchrresearch, thisrresearch is a qualitative research with a psychological approach, the data collection technique is interview, where this interview is conducted by obtaining data from suscatin participants. implementation of this research. The primary data in this study were suscatin participants and the secondary was a marriage advisor at the North Sinjai KUA. In terms of managing and analyzing it, the author uses data reduction, data display and conclusion. The results of this study can conclude that this suscatin is very important to implement because it can provide knowledge for participants, both prospective husbands and prospective wives, how to deal with households with their partners, then there are many benefits in implementing suscatin where they understand each other's responsibilities, provide solutions what is good in a household, how to overcome conflict in a household and the duties of a husband as well as for his wife. Basically, this suscatin is important to carry out even though the time is short, but it can provide material for suscatin participants how to deal with married life with a partner. The hope of the suscatin participants that the implementation of suscatin is to add material and later time is consistent with the time that has been set so that participants do not accidentally arrive late.